If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 3(x + -7) = -36 Reorder the terms: -8x + 3(-7 + x) = -36 -8x + (-7 * 3 + x * 3) = -36 -8x + (-21 + 3x) = -36 Reorder the terms: -21 + -8x + 3x = -36 Combine like terms: -8x + 3x = -5x -21 + -5x = -36 Solving -21 + -5x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -5x = -36 + 21 Combine like terms: -21 + 21 = 0 0 + -5x = -36 + 21 -5x = -36 + 21 Combine like terms: -36 + 21 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 8.5x+1.1=2.5x+2.25 | | -7-3x=4 | | 4(2x+6)=72 | | -4x-11=3x+10 | | 3(y^2-y+1)= | | -2x-5x=21 | | 4v^2+13v+5=-5 | | 12x-10=-2+12 | | -5v-8-10-8v=0 | | 5x+7+22=EF | | 16y-10=10y-5 | | (x-6)(x+5)=12 | | 18-(-f)=101 | | 10x=0.3-9.1 | | 28m-32x=92 | | -8-3x=16 | | -6/5=-6/5n | | 1.8a-5=2.3 | | 15x+10+12-12x=3x | | x+8=-3x-7 | | 8k+2k+16=6k+8k | | -(7xy-12)+2(5xy+7)= | | -5k(2+7)=-35k+(-10k) | | 4x+5=4x+3 | | b+3(6)=b-3(7) | | 2n-2(4n+5)=6(n-3)-8 | | X+50=25 | | 6x-59=4x-20 | | 40x+3=180 | | (6x-1)=(3x)+(2x+1) | | 3x+x-20=220 | | 9x+3x=48 |